From Entrepreneurs to Startups: Rethinking Pivot Decisions through a Systematic Literature Review - Lydia Apriliani; Muhammad Amirulafiq Juhari (TIJAB (The International Journal of Applied Business), 2026)
Background: Despite the prevalence of "pivot" in entrepreneurial practice, the concept remains theoretically fragmented. Extant literature lacks consensus on the constitutive elements of a pivot and the boundary conditions that trigger strategic redirection, leading to conceptual "fuzziness" that hinders cumulative knowledge building. Objective: This study aims to bridge these conceptual gaps by synthesizing the fragmented pivot literature. Specifically, we move beyond descriptive summaries to develop a multidimensional definition and a processual framework that explains how founders navigate business model failure. Method: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we conducted a systematic review of 86 peer-reviewed articles published between 2008 and 2024. Data were analyzed using bibliometric techniques and thematic content analysis to map the field's evolution. Results: We identify four dominant research streams: design-oriented pivots, cognitive mechanisms, negotiation dynamics, and environmental influences. Theoretically, we contribute by redefining the pivot as a strategic response to actual or anticipated business model failure, a shift involving resource reallocation and core model transformation. Furthermore, we propose a novel four-phase pivot framework: (1) Recognition, (2) Option Generation, (3) Seizing and Testing, and (4) Reconfiguration. Conclusion: This review synthesizes diverse pivot concepts, reconciles fragmented terminology, and highlights the cognitive and contextual dimensions of entrepreneurial decision-making. By integrating theoretical perspectives and empirical insights, the study offers a comprehensive foundation for future research on entrepreneurial pivots and strategic adaptation in dynamic environments. Keywords: Pivot, Decision-making, Startup, Entrepreneurial judgment, Innovation JEL code: L26, D81, M13, L21, and O31